1998
DOI: 10.1021/jp982827+
|View full text |Cite
|
Sign up to set email alerts
|

Toward Infinite-Dilution Voltammetry

Abstract: Steady-state microelectrode voltammetry has been used to obtain reversible half-wave potentials for the two reduction waves of 7,7,8,8-tetracyanoquinodimethane (TCNQ) and the oxidation wave of ferrocene in acetonitrile with concentrations of tetramethylammonium hexafluorophosphate electrolyte ranging from 1 to 70 mM. The dependence of the first half-wave potential of TCNQ, referred to the half-wave potential of ferrocene, on ionic strength was adequately accounted for by changes in activity coefficients of fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
39
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 20 publications
7
39
0
Order By: Relevance
“…The first reduction peak for each compound, R 1 , is an overall two-electron process that is irreversible and diffusion controlled. For 1a (X = H) no additional reduction peaks were seen in scans to −3.1 V but for 1b (X = CN) a reversible couple (R 2 /O 2 ) appears with E ° equal to −2.87 V . This potential is identical with that found for reduction of p -cyanocumene, 2b .…”
Section: Resultssupporting
confidence: 73%
“…The first reduction peak for each compound, R 1 , is an overall two-electron process that is irreversible and diffusion controlled. For 1a (X = H) no additional reduction peaks were seen in scans to −3.1 V but for 1b (X = CN) a reversible couple (R 2 /O 2 ) appears with E ° equal to −2.87 V . This potential is identical with that found for reduction of p -cyanocumene, 2b .…”
Section: Resultssupporting
confidence: 73%
“…Previous research has observed IP formation between solute ions and supporting electrolytes or ionic liquids, and the measurements showed that the reduction potential was increased by this effect. For example, the association free energy of the IP between TBA + and 9,9-dihexyl-9 H -fluorene-2-carbonitrile (F1CN) was measured to be −0.29 eV in tetrahydrofuran (THF) . Theoretical investigations by Fry examined the structures and thermodynamics of various IPs.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, we determined the infinite-dilution standard potentials, E ° 1 and E ° 2 , for TCNQ (referred to the infinite-dilution standard potential for the ferrocene/ferrocenium couple) by using steady-state microelectrode voltammetry at low ionic strength in well-supported solutions (ratio of electrolyte to TCNQ concentration equal to 10). In the course of these studies, we noted an unusual asymmetry in the shape of the second steady-state voltammetric wave under certain experimental conditions.…”
mentioning
confidence: 99%